Pengaruh Analisis Jabatan Tunjangan Kinerja dan Kepemimpinan Terhadap Kinerja Pegawai (Study Kasus Pada Pegawai Dinas Pariwisata dan Kebudayaan Kabupaten Lumajang) - Aji Achmad Syaifullah; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study was to determine and analyze job analysis, performance allowances, and leadership at the Tourism and Culture Office of Lumajang Regency. The population in this study amounted to 163 and the sample taken amounted to 41 respondents. Collecting data through the distribution of questionnaires. Data analysis in this study used SPSS Version 16. The sampling technique used quantitative methods and linear test data testing techniques used were validity test, reliability test, classical assumption test, multiple regression test and hypothesis testing.The results of the analysis show that job analysis, performance allowances and leadership simultaneously have an effect on employee performance, partially not significant effect on employee performance, but job analysis and performance allowances have an influence on employee performance at the Lumajang Regency Tourism and Culture Office. Keywords: Job analysis, Performance allowances, Leadership and Employee   Performance.